Les procès d’animaux en Lorraine (XIVe-XVIIIe siècles) - Laurent Litzenburger (Criminocorpus)
Lorraine and Barrois archives deliver – in the current state of research – thirty-four mentions of animals and insects trials that are part of a broad chronological range, beginning in the mid-fourteenth century and finishing during the first third of the eighteenth century. Such trials took place across the Christian West since the mid-thirteenth century. Examples are rare and were long been considered by historians as a epiphenomena, betraying some archaism of ancient societies. To understand this phenomenon, it is necessary to consider the cultural context that makes it possible. This is part of the long-term revival of antiquity to the humanist tought and the emergence of the Enlightenment. How to explain that, during these period, societies found it perfectly reasonable to prosecute animals and insects?